Micro Waqf Bank: An Innovation Of Islamic Microfinance Institutions In Indonesia? - kalamika, Arin (West Science Social and Humanities Studies, 2024)
The innovation developed by Islamic financial institutions through Micro Waqf Bank has caused a new problem instead of overcoming the existing one. The problem is in relation to the institutional form which aims to be free from interest and riba. This study employed literature review method with supporting secondary data taken from trusted state institutions. The results indicated that the innovation carried out through the concept of Micro Waqf Bank is free from interest and riba not only because of the deposit regulation pertaining to Islamic banking institutions. Even the deposit yield under the name of profit sharing is considered riba as well. The result of the innovation is not economically profitable for the bank. On the contrary, it suffers a significant loss because it cannot invest its large assets. Moreover, the invested funds can trigger inflation of currency exchange rate as a result of the time frame of debts. In fact, deposits that are channeled into profitable business units will likely strengthen Micro Waqf Bank which is free from interest and riba. Moreover, if the deposits are managed properly, Micro Waqf Bank can obtain funds greater than the stipulated interest rate.